Merry Christmas big hungry bear! - Wood, Don, 1945-; Wood, Audrey (New York : Blue Sky Press, 2002)
A little mouse shares the Christmas spirit with the big hungry bear he once feared, after realizing the bear will have no presents.
Publisher's Weekly
Booklist
3.8
K-3
Keywords: Bears -- Fiction; Christmas -- Fiction; Mice -- Fiction; Bears -- Fiction; Christmas -- Fiction; Mice -- Fiction